Acute uncomplicated appendicitis study: rationale and protocol for a multicentre, prospective randomised controlled non-inferiority study to evaluate the safety and effectiveness of non-operative management in children with acute uncomplicated appendicitis. Issue 12 (21st December 2016) - Xu, Jane; Liu, Yingrui Cyril; Adams, Susan; Karpelowsky, Jonathan
Abstract : Introduction: This article presents an overview of a prospective randomised controlled non-inferiority study designed to evaluate the safety and effectiveness of non-operative management (NOM) with operative management in children with acute uncomplicated appendicitis (AUA). Here, we present the study protocol for this APRES study, a multicentre Australian study. The rationale and details of future analysis, in particular, non-inferiority calculations, cost-effectiveness, feasibility and acceptability of each intervention. Design: A multicentre, prospective randomised controlled clinical trial, conducted in 2 Australian tertiary paediatric hospitals. Participants: Children who meet the inclusion criteria of an age between 5 and 15 years and a clinical diagnosis of AUA will be invited to participate, and after consent will be randomised via a computer-based program into treatment groups. The study started in June 2016, and the target recruitment is 220 patients. Interventions: Children in the control group will be treated with prophylactic antibiotics and appendicectomy, and those in the intervention group will be treated with antibiotic therapy alone. Primary outcome measures include unplanned or unnecessary operation and complications at 30 days. Secondary outcomes include longer term complications within 1 year, length of stay, time off work and school analgesic requirements and cost. Analysis: Data analyses will be on the intention-to-treat principle using non-inferiority analysis. Analysis will include the Pearson χ 2 test for categorical variables and independent sample t-test or Mann-Whitney test for continuous variables. Non-inferiority for NOM will be tested using 1-sided Wald tests with an α level of 0.05. Ethics and dissemination: The research has been approved by the Human Research Ethics Committee of the Sydney Children's Hospital Network. In addition, results will be reported through academic journals, seminars and conference presentations. Trial registration numbers: NCT02795793 ; ACTRN12616000788471 .